Cooperation Behavior of Opinion Leaders and Official Media on the Governance of Negative Public Opinion in the Context of the Epidemic: An Evolutionary Game Analysis in the Perspective of Prospect Theory - Jing Wei; Lijun Wang; Hengmin Zhu; Weidong Huang (Complexity)
The reach of online information transmission has expanded due to the rapid growth of social software and Internet technology, and the negative information generated during the COVID-19 outbreak can confuse the public. Therefore, a new challenge in the prevention and control of epidemics is how to supervise negative public perceptions. This study differentiates negative public opinion communication stages through practical cases and is based on the life cycle hypothesis. In order to examine the evolution and stability tactics of each game subject in each stage of the evolution of public opinion, a three-way evolution game model comprising social platform operators, official media, and opinion leaders is created on the basis of prospect theory. Finally, the advanced epidemic model is used to verify the important impact of cooperation between official media and opinion leaders on curbing the transmission of negative public opinion. It is found that the perceived value of game players on income and loss will significantly affect the trend of the tripartite game strategy, and the cooperative behavior of official media and opinion leaders can effectively promote the benign development of online public opinion.